Papers in and Papers out of the Spotlight: Comparative Bibliometric and Altmetrics Analysis of Biomedical Reports with and without News Media Stories - Artemis Chaleplioglou (Publications)
For decades, the discoverability and visibility of a paper relied on the readership of the academic journal where the publication was issued. As public interest in biomedicine has grown, the news media have taken on an important role in spreading scientific findings. This investigation explores the potential impact of news media stories on the citations and altmetrics of a paper. A total of 2020 open-access biomedical research papers, all published in the same year, 2015, and in journals with an impact factor between 10 and 14, were investigated. The papers were split into two groups based on the sole criterion of receiving or not receiving news media coverage. Papers with news media coverage accounted for 44% of the total. They received, on average, 60% more citations, 104% more blogs, 150% more X posts, 106% more Facebook reports, 40% more Wikipedia references, 85% more videos, and 51% more Mendeley readers than papers without news media coverage. The correlation between news media outlets and increased citations and altmetrics is evident. However, the broader societal impact of news media coverage, in terms of bringing scientific matters or discoveries to the public eye, appears to be more robust when compared to the reactions of the scientific community.